Composite modified sawdust machine oil filter element material and preparation method thereof

CN122955274APending Publication Date: 2026-10-23JILIN AGRICULTURAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611462268.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

通过PEI、SiO2的复合改性,有效解决了木屑基滤芯材料亲油性差,过滤效率低的问题

Benefits of technology

本发明中通过逐级共价键合改性,解决改性过程中PEI和SiO2脱落的问题,从而获得亲油性好、结构稳定、过滤效率高的机油滤芯材料。在机油中对于Fe和Al的分离去除率分别达到91.4%和90.5%,胶质的分离去除率达到62.9%,材料具有优异的耐高温性能,耐压降循环稳定性和耐磨粒冲刷能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a composite modified sawdust machine oil filter element material and a preparation method thereof, belongs to the technical field of filtering and separating materials, and is characterized in that the sawdust is subjected to alkali pretreatment, then grafted and modified by polyethylene imine (PEI) to obtain sawdust-PEI, then subjected to SiO2 loading modification by using a neutral silica sol solution, and finally subjected to post-treatment by using methyltrimethoxysilane (MTMS) to obtain the PEI and SiO2 composite modified sawdust machine oil filter element material. In the application, the PEI and SiO2 are modified by means of step-by-step covalent bonding, so that the problem of PEI and SiO2 falling off in the modification process is solved, and thus the machine oil filter element material with good lipophilicity, stable structure and high filtering efficiency is obtained. In the machine oil, the removal rates of Fe and Al are 91.4% and 90.5% respectively, the removal rate of colloid is 62.9%, and the material has excellent high-temperature resistance, pressure drop cycle stability and wear particle erosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of filtration and separation materials technology, specifically to PEI and nano-SiO2 composite modified wood chip oil filter material and its preparation method. Background Technology

[0002] As internal combustion engines develop towards higher power, lower emissions, and longer lifespans, engine lubrication systems place increasingly higher demands on the filtration accuracy, contaminant holding capacity, temperature stability, and service life of oil filters. The core function of an oil filter is to trap contaminants such as metal particles, oxidized colloids, and dust impurities in the circulating oil, preventing them from entering the engine's friction surfaces and causing abnormal wear. It is a crucial component for ensuring reliable engine operation.

[0003] Wood chips, as a widely available and inexpensive natural porous fiber material, possess advantages such as large specific surface area, rich pore structure, and biodegradability, making them a promising candidate for use in oil filter materials. However, unmodified virgin wood chips have several inherent drawbacks, making them unsuitable for direct application in oil filtration: First, the surface of wood chips contains a large number of hydrophilic hydroxyl groups and hydrophobic lignin, resulting in heterogeneous interfacial properties. In high-temperature oil, they are prone to swelling and deformation, leading to clogging of filter channels and a rapid increase in pressure drop. Second, the low density of active functional groups on the surface of wood chips results in insufficient adsorption and retention capacity for micron-sized metal abrasive particles and oxidized colloids in the oil, making it difficult to meet the filtration efficiency requirements of operating conditions. Therefore, it is essential to perform targeted modification of wood chips to optimize their interfacial properties, structural stability, and adsorption performance in order to adapt them to the operating conditions of oil filters.

[0004] Existing technologies for modifying wood chips mainly include alkali treatment modification, organic polymer grafting modification, and inorganic nanoparticle loading. However, these wood chip modifications are almost exclusively developed for water treatment, heavy metal adsorption, and other aqueous phase adsorption scenarios. Their modification goals and performance orientations are fundamentally different from those of oil filtration. Directly applying them to oil filtration faces many insurmountable technical obstacles. For example, in an aqueous environment, grafted PEI molecules extend, fully exposing amino sites, enabling efficient chelation of dissolved heavy metal ions. However, in non-polar engine oil media, PEI, being a highly polar polymer, suffers from severe polarity mismatch with the oil phase, leading to easy chain aggregation and deactivation of numerous amino active sites, resulting in a significant decrease in adsorption efficiency. Furthermore, under the continuous shearing action of high-temperature, high-pressure oil flow, the Schiff base bonds between PEI and the matrix are prone to breakage, causing interfacial peeling and overall detachment of the PEI layer, resulting in a rapid decline in filtration performance. In an aqueous environment, nano-SiO2 loading can increase specific surface area and adsorption capacity, and since there are no hard abrasive particles in the water flow, a small amount of detachment poses no secondary harm. However, in engine oil conditions, the circulating oil carries a large number of hard metal abrasive particles such as Fe and Al, which, under pressure differential, rapidly scour the filter media surface. Physically adsorbed nano-SiO2 particles are easily eroded and lost, leading not only to a rapid decline in filtration performance but also causing the detached hard SiO2 particles to enter the oil circulation, forming secondary abrasive particles and exacerbating wear on engine components. Summary of the Invention

[0005] Based on existing technology, the purpose of this invention is to provide a composite modified wood chip oil filter material. Through composite modification with PEI and SiO2, the problems of poor oleophilicity and low filtration efficiency of wood chip-based filter materials are effectively solved.

[0006] Another objective of this invention is to provide a method for preparing the aforementioned oil filter element material. This method solves the problem of PEI and SiO2 detachment during the modification process through stepwise covalent bonding modification, thereby obtaining an oil filter element material with good oleophilicity, stable structure, and high filtration efficiency.

[0007] The objective of this invention is achieved through the following technical solution: A method for preparing a composite modified wood chip oil filter material is characterized by: pretreating wood chips with alkali, then grafting and modifying them with polyethyleneimine (PEI) to obtain wood chip-PEI, then modifying them with SiO2 loading using a neutral silica sol solution, and finally post-treating them with methyltrimethoxysilane (MTMS) to obtain a composite modified wood chip oil filter material of PEI and SiO2.

[0008] Furthermore, the alkali pretreatment involves weighing sawdust, adding it to a NaOH solution, stirring at 55-65 °C for 5-7 hours, and after the reaction is complete, washing and drying to obtain alkali-treated sawdust.

[0009] Furthermore, the ratio of sawdust to NaOH solution is 1g:4.5~5.5mL, and the concentration of NaOH solution is 1mol / L.

[0010] Furthermore, the grafting modification involves adding alkali-treated wood chips to a polyethyleneimine solution, then adding glutaraldehyde, shaking at 30 ℃ for 6 h, filtering, rinsing with distilled water until neutral, and drying to obtain PEI-modified wood chips (wood chips-PEI).

[0011] Furthermore, the ratio of the amount of alkali-treated wood chips to polyethyleneimine solution is 1g:22~26mL, the concentration of polyethyleneimine solution is 28~32 g / L, and the volume fraction of glutaraldehyde added in the solution is 0.4~0.6%.

[0012] Furthermore, the SiO2 loading modification involves first anchoring the wood chips-PEI with γ-glycidyl etheroxypropyltrimethoxysilane (EPPTMS), and then placing it in a neutral silica sol solution for loading reaction.

[0013] Furthermore, the anchoring treatment involves adding sawdust-PEI to dry DMF and mechanically stirring to disperse it. Then, 30 mL of γ-glycidoxypropyltrimethoxysilane (EPPTMS) is slowly added dropwise at a rate of 1-2 mL / min. The mixture is stirred for 10 min and then reacted in an oil bath at 75-85 °C with mechanical stirring for 12-16 h. After washing and drying, EPPTMS-anchored sawdust-PEI is obtained.

[0014] Furthermore, the ratio of the wood chips-PEI, EPPTMS and DMF is 3.5~4.5g:3mL:97mL.

[0015] Furthermore, during the loading reaction, a 4-6% neutral silica sol solution is prepared, and EPPTMS-anchored wood chips-PEI are added to the solution, and the reaction is carried out at 75-85 °C for 24 h.

[0016] Furthermore, the ratio of the amount of EPPTMS-anchored wood chips-PEI to the neutral silica sol solution is 1g:20~30mL.

[0017] Further, in the post-treatment, methyltrimethoxysilane is weighed at 2% to 5% of the dry silica mass in the neutral silica sol solution, dissolved in 3 to 5 times its volume of anhydrous ethanol, and the pH is adjusted to 4.5 to 5.0 by adding dilute acetic acid dropwise. The solution is then pre-hydrolyzed at room temperature for 20 to 40 minutes. The pre-hydrolyzed solution is then added dropwise to the silica-modified reaction system, and the reaction is continued at 75 to 85 °C for 3 to 6 hours.

[0018] Most specifically, a method for preparing a composite modified wood chip oil filter material is characterized by the following steps: S1. Wood chip pretreatment Weigh sawdust and add it to a 1 mol / L NaOH solution. Stir at 55-65 °C for 5-7 h. After the reaction is complete, filter with a sieve and wash with distilled water until neutral. Dry at 45-55 °C to obtain alkali-treated sawdust. The ratio of sawdust to NaOH solution is 1 g: 4.5-5.5 mL. S2.PEI Modification Alkali-treated sawdust was added to a polyethyleneimine solution with a concentration of 28-32 g / L, followed by the addition of glutaraldehyde to make the volume fraction of glutaraldehyde in the solution 0.5%. The solution was then shaken at 30 ℃ for 6 h, filtered, rinsed with distilled water until neutral, and finally dried in an oven at 45-55 ℃ to obtain PEI-modified sawdust (sawdust-PEI). The ratio of alkali-treated sawdust to polyethyleneimine solution was 1 g: 22-26 mL. S3. Silica Modification (1) Add sawdust-PEI to dry DMF and mechanically stir to disperse. Add 30 mL of γ-glycidoxypropyltrimethoxysilane (EPPTMS) slowly at a rate of 1-2 mL / min. Continue stirring for 10 min. In an oil bath at 75-85 °C, mechanically stir and react for 12-16 h. After the reaction is complete, filter and collect sawdust. Wash with anhydrous ethanol 4 times and then with deionized water 2 times. Place the washed sawdust in a vacuum drying oven at 60 °C and dry for 6 h to obtain EPPTMS-anchored sawdust-PEI. The ratio of sawdust-PEI, EPPTMS and DMF is 3.5-4.5 g: 3 mL: 97 mL. (2) Prepare a 4-6% neutral silica sol solution and add the EPPTMS-anchored wood chips-PEI to the solution. React at 80 °C for 24 h. The ratio of the amount of EPPTMS-anchored wood chips-PEI to the amount of neutral silica sol solution is 1 g: 20-30 mL. S4. Post-processing Weigh 2%–5% of the dry silica mass in the neutral silica sol solution as methyltrimethoxysilane, dissolve it in 3–5 times its volume of anhydrous ethanol, adjust the pH to 4.5–5.0 by adding dilute acetic acid dropwise, and pre-hydrolyze at room temperature for 20–40 min. Then add the pre-hydrolyzed solution dropwise to the silica modification reaction system, and continue the reaction at 75–85 °C for 3–6 h. Wash four times with anhydrous ethanol, then wash twice with deionized water, and vacuum dry at 60 °C to obtain the composite modified wood chip oil filter material.

[0019] When PEI and SiO2 are used alone to modify wood chips, PEI and SiO2 will fall off under oil-conditioning conditions, resulting in low overall filtration efficiency and poor cycle stability of the material.

[0020] In this invention, PEI is covalently grafted onto the surface of alkali-treated sawdust. Both lignocellulose and nano-SiO2 are rigid materials with significant modulus differences; direct bonding would generate extremely high interfacial stress, making them prone to peeling off in sheets under temperature fluctuations and fluid erosion. The flexibility of the long PEI chains effectively disperses this interfacial stress, acting as an "elastic buffer layer" and significantly improving the anti-peeling performance of the SiO2 layer. After anchoring with EPPTMS, SiO2 grows in situ at the anchoring points on the PEI organic layer surface, uniformly dispersing to form a discrete porous SiO2 network structure. This fixes the PEI between the fiber matrix and SiO2, preventing direct erosion of the PEI layer by high-temperature, high-pressure oil, and significantly reducing the damage to the PEI-matrix interface caused by oil shear force. Simultaneously, it restricts the swelling and shrinkage of PEI molecular chains in the non-polar oil phase, maintaining the exposure of amino adsorption sites. Furthermore, SiO2 has a much higher thermal conductivity than PEI, which can quickly disperse local heat and prevent thermal degradation and chemical bond breakage of the PEI layer. The low coefficient of thermal expansion of SiO2 can constrain the thermal expansion of PEI, reduce interfacial thermal stress, and decrease the probability of glutaraldehyde Schiff base bond breakage. Overall, this improves the structural stability and reduces the risk of SiO2 shedding from PEI during use.

[0021] Before SiO2 modification, the wood chips-PEI were anchored with EPPTMS. The epoxy end of EPPTMS underwent a ring-opening addition reaction with the primary / secondary amines on the PEI surface to generate stable CN covalent bonds. The reaction can be carried out efficiently in the liquid phase at 30~80℃. At this time, the trimethoxysilane end of the silane is exposed to the outside. In the subsequent aqueous system, the methoxy group is hydrolyzed to generate silanol groups, which undergo a dehydration condensation reaction with the silanol groups on the surface of nano-SiO2 in the neutral silica sol to form Si-O-Si covalent bonds. Finally, a fully continuous covalent bond network of wood chip matrix-PEI layer-epoxy ring-opening-silane chain-nano-SiO2 is formed, which effectively improves the interfacial bonding strength between PEI and SiO2.

[0022] A PEI and nano-SiO2 composite modified wood chip oil filter material is characterized by: pretreating wood chips with alkali, then grafting and modifying them with polyethyleneimine (PEI) to obtain wood chip-PEI, then modifying them with SiO2 loading using a neutral silica sol solution, and finally post-treating them with methyltrimethoxysilane (MTMS) to obtain the PEI and SiO2 composite modified wood chip oil filter material.

[0023] Furthermore, the alkali pretreatment involves weighing sawdust, adding it to a NaOH solution, stirring at 55-65 °C for 5-7 hours, and after the reaction is complete, washing and drying to obtain alkali-treated sawdust.

[0024] Furthermore, the ratio of sawdust to NaOH solution is 1g:4.5~5.5mL, and the concentration of NaOH solution is 1mol / L.

[0025] Furthermore, the grafting modification involves adding alkali-treated wood chips to a polyethyleneimine solution, then adding glutaraldehyde, shaking at 30 ℃ for 6 h, filtering, rinsing with distilled water until neutral, and drying to obtain PEI-modified wood chips (wood chips-PEI).

[0026] Furthermore, the ratio of the amount of alkali-treated wood chips to polyethyleneimine solution is 1g:22~26mL, the concentration of polyethyleneimine solution is 28~32 g / L, and the volume fraction of glutaraldehyde added in the solution is 0.4~0.6%.

[0027] Furthermore, the SiO2 loading modification involves first anchoring the wood chips-PEI with γ-glycidyl etheroxypropyltrimethoxysilane (EPPTMS), and then placing it in a neutral silica sol solution for loading reaction.

[0028] Furthermore, the anchoring treatment involves adding sawdust-PEI to dry DMF and mechanically stirring to disperse it. Then, 30 mL of γ-glycidoxypropyltrimethoxysilane (EPPTMS) is slowly added dropwise at a rate of 1-2 mL / min. The mixture is stirred for 10 min and then reacted in an oil bath at 75-85 °C with mechanical stirring for 12-16 h. After washing and drying, EPPTMS-anchored sawdust-PEI is obtained.

[0029] Furthermore, the ratio of the wood chips-PEI, EPPTMS and DMF is 3.5~4.5g:3mL:97mL.

[0030] Furthermore, during the loading reaction, a 4-6% neutral silica sol solution is prepared, and EPPTMS-anchored wood chips-PEI are added to the solution, and the reaction is carried out at 75-85 °C for 24 h.

[0031] Furthermore, the ratio of the amount of EPPTMS-anchored wood chips-PEI to the neutral silica sol solution is 1g:20~30mL.

[0032] Further, in the post-treatment, methyltrimethoxysilane is weighed at 2% to 5% of the dry silica mass in the neutral silica sol solution, dissolved in 3 to 5 times its volume of anhydrous ethanol, and the pH is adjusted to 4.5 to 5.0 by adding dilute acetic acid dropwise. The solution is then pre-hydrolyzed at room temperature for 20 to 40 minutes. The pre-hydrolyzed solution is then added dropwise to the silica-modified reaction system, and the reaction is continued at 75 to 85 °C for 3 to 6 hours.

[0033] The present invention has the following technical effects: This invention addresses the issue of PEI and SiO2 detachment during the modification process through stepwise covalent bonding modification, thereby obtaining an oil filter material with good oleophilicity, structural stability, and high filtration efficiency. The material achieves separation and removal rates of 91.4% for Fe and 90.5% for Al in engine oil, and 62.9% for colloids. It also exhibits excellent high-temperature resistance, pressure drop cycle stability, and resistance to abrasive erosion. Detailed Implementation

[0034] The present invention will be specifically described below through embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.

[0035] Example 1 A method for preparing a composite modified wood chip oil filter element material, comprising the following steps: S1. Wood chip pretreatment Weigh 100 g of sawdust and add it to 500 mL of 1 mol / L NaOH solution. Stir at 60 °C for 6 h. After the reaction is complete, filter through a sieve and wash with distilled water until neutral. Dry in an oven at 50 °C for 12 h to obtain alkali-treated sawdust. S2.PEI Modification Take 20 g of dried alkali-treated sawdust, add 500 mL of a 30 g / L polyethyleneimine solution, then add glutaraldehyde to make the volume fraction of glutaraldehyde in the system 0.5%, and shake at 30 ℃ for 6 h. Then filter, wash with distilled water until neutral, and finally dry in an oven at 50 ℃ to obtain PEI-modified sawdust (sawdust-PEI). S3. Silica Modification (1) Add about 970 mL of dry DMF to a dry 2 L three-necked flask, add 40 g of dry sawdust-PEI to the flask, stir mechanically to disperse it evenly, slowly add 30 mL of EPPTMS to the flask at a speed of 1.5 mL / min, continue stirring for 10 minutes to mix it evenly, react mechanically in an oil bath at 80 ℃ for 14 h, after the reaction is completed, filter and collect sawdust, wash 4 times with anhydrous ethanol, then wash 2 times with deionized water, place the washed sawdust in a vacuum drying oven at 60 ℃ and dry for 6 h to obtain EPPTMS anchored sawdust-PEI; (2) Prepare 1 L of 5% neutral silica sol solution (pH 7.0), and add the EPPTMS-anchored wood chips-PEI to the solution, and react at 80 °C for 24 h; S4. Post-processing Methyltrimethoxysilane was weighed at 4% of the dry silica mass in the neutral silica sol solution and dissolved in 4 times its volume of anhydrous ethanol. The pH was adjusted to 4.8 by adding dilute acetic acid dropwise, and the solution was pre-hydrolyzed at room temperature for 30 min. The pre-hydrolyzed solution was then added dropwise to the silica modification reaction system and the reaction was continued at 80 °C for 4 h. The solution was washed 4 times with anhydrous ethanol and then 2 times with deionized water. The composite modified wood chip oil filter material was obtained by vacuum drying at 60 °C.

[0036] Comparative Example 1 Compared with Example 1, the difference is that in step S3, EPPTMS-anchored wood chips-PEI were not prepared, but the wood chips-PEI were directly immersed in a neutral silica sol solution for reaction (i.e. step (1) was omitted in step S3, and step (2) was directly performed). The remaining steps are the same as in Example 1.

[0037] Comparative Example 2 Compared with Example 1, the difference is that after the alkali pretreatment in step S1, the SiO2 modification in step S3 is carried out first to prepare wood chips-SiO2, and then the PEI modification in step S2 is carried out. The remaining steps are the same as in Example 1.

[0038] Comparative Example 3 Compared with Example 1, the difference is that in step S4, MTMS was not used for end-capping treatment. Instead, the product was washed until neutral and then dried.

[0039] The properties of the materials from Example 1, the intermediate product of Example 1 (wood chips-PEI), Comparative Examples 1-3, and the intermediate product of Comparative Example 2 (wood chips-SiO2) were compared through corresponding tests: (a) Product interface bonding strength test The high-temperature ashing gravimetric method involves ashing the sample in a muffle furnace at 800 °C for 4 h, weighing the ash content, and calculating the percentage of SiO2 in the total mass. Elemental analysis (EA) is used to determine the nitrogen content of the sample.

[0040] The interfacial bonding strength was then reflected by testing the SiO2 and PEI detachment rate using the ultrasonic oscillation detachment method: 1 g of sample was immersed in 50 mL of anhydrous ethanol and ultrasonically oscillated at 40 kHz and 200 W for 30 min. After filtration and drying, the sample was weighed. The SiO2 detachment rate was calculated by the change in the mass fraction of SiO2 in the solid before and after ultrasonic testing (the effect of the coupling agent on the test results is minimal and can be ignored).

[0041] In the formula, w0: Initial mass fraction of SiO2 in the sample before ultrasound (measured by high-temperature ashing method); w 1: The remaining mass fraction of SiO2 in the sample after ultrasonication (measured by the same method).

[0042] The change in nitrogen content of the solid sample was tested by elemental analysis, and the PEI shedding rate was also calculated. The results are shown in Table 1.

[0043] Table 1: Ultrasonic shedding rates of SiO2 and PEI in each group of products

[0044] (II) Basic Filtration Performance Test: Following the test principle of GB / T 8243 "Test Method for Full-Flow Oil Filters for Internal Combustion Engines", a small filter media performance testing device was constructed. 0.4g of the product was weighed and evenly spread on a supporting screen, gently scraped to ensure a uniform filter layer thickness. A 200-mesh stainless steel pressure mesh was then placed on the surface, the clamps were tightened and sealed, forming a sealed filter media test clamp with an effective filtration area of ​​10 cm². Simulated contaminated engine oil was prepared using 150SN base oil for filtration performance testing: containing 100 mg / L of Fe powder (below 5 μm), 50 mg / L of Al powder, and 200 mg / L of oxidized colloids.

[0045] 1. Original filtration efficiency test The filter media has an effective filtration area of ​​10 cm², and the oil flow rate is 5 L / min. After filtration for 30 min, the concentrations of Fe and Al particles (ICP-OES) and the content of colloids (GB / T 8926-2012) in the inlet and outlet oils were tested, and the removal rate was calculated. Removal rate (%) = (Inlet concentration - Outlet concentration) / Inlet concentration × 100% 2. Initial pressure drop test With a fixed oil flow rate of 5 L / min, the steady-state pressure difference across the filter media is measured, which is the initial pressure drop, expressed in kPa.

[0046] 3. Dirt tolerance Simulated contaminated engine oil is continuously introduced. The test is stopped when the pressure drop rises to twice the initial pressure drop. The total mass of contaminants trapped per unit area of ​​filter media is calculated, which is the dirt holding capacity (unit: g / m²). 2 The dirt-holding capacity and service life were verified. The results are shown in Table 2.

[0047] Table 2

[0048] (III) Operating condition stability test 1. High temperature resistance test The filter media sample was immersed in 150SN base oil (Fe content 100 mg / L) and aged at 135 ℃ for 192 h. After aging, the sample was washed and dried, and the following were tested: ① functional group retention rate (FT-IR infrared spectrum characteristic peak area ratio); ② Fe removal efficiency retention rate; ③ SiO2 / PEI shedding rate. The results are shown in Table 3.

[0049] Table 3:

[0050] 2. Withstand voltage drop cycle stability The pressure was cycled 1000 times at a working pressure of 0.35 MPa (one cycle consists of pressurization-holding-depressurization). After the cycle, the SiO2 shedding rate, PEI shedding rate, and Fe removal efficiency retention rate were tested. The results are shown in Table 4.

[0051] Table 4:

[0052] 3. Resistance to abrasive erosion A 150SN base oil containing 500 mg / L of 3-5 μm Fe abrasive particles was prepared and circulated to flush the filter media for 100 h under a pressure differential of 0.3 MPa. Tests were conducted on: ① SiO2 shedding rate; ② secondary SiO2 particle concentration (ICP) in the outlet oil (mg / L); ③ Fe removal efficiency retention rate after flushing. The results are shown in Table 5.

[0053] Table 5:

[0054] As can be seen from the data in the table above, in Comparative Example 1 without EPPTMS anchoring, SiO2 and PEI are only physically bonded by hydrogen bonds and van der Waals forces, resulting in numerous bonding breakpoints at the interface. Under the scouring of oil flow, SiO2 particles rapidly detach, failing to form a stable inorganic protective layer. Simultaneously, PEI remains directly exposed to the oil phase, and the problems of molecular shrinkage and interface peeling remain unresolved. Furthermore, the dual hydrophilic modification further increases the pressure drop. In this invention, after constructing a covalent bridge using EPPTMS, a continuous covalent network of "PEI-CN bond-silane chain-Si-O-Si bond-SiO2" is formed, increasing the interfacial bonding strength by an order of magnitude. Simultaneously, the in-situ growth of SiO2 forms a discrete porous outer layer, which both physically protects the PEI layer and retains mass transfer channels, achieving a synergistic effect of "inner layer chemical adsorption + outer layer physical retention."

[0055] In Comparative Example 2, a reverse process of first loading SiO2 and then grafting PEI was used. Without PEI as an intermediate layer, EPPTMS reacted directly with the cellulose hydroxyl groups on the surface of the wood chips. However, the hydroxyl group density was low, and its reactivity with epoxy groups was much lower than that with amino groups, resulting in a low silane grafting amount. At the same time, the bonding direction was reversed (siloxane end attached to hydroxyl group, epoxy end facing outward), so SiO2 could not form covalent bonds with the epoxy end, and hydrogen bonding still dominated, resulting in limited improvement in overall bonding strength. On this basis, further cross-linking and covalently grafting PEI failed to form effective covalent cross-linking between siloxane hydroxyl groups and PEI amino groups. PEI was only physically adsorbed by weak hydrogen bonds, resulting in extremely weak bonding force, and it quickly detached under the scouring of the oil phase. At the same time, the functional layers were completely reversed: PEI was on the outermost layer and directly contacted the oil phase, resulting in the reappearance of defects such as molecular curling and inactivation, strong hydrophilicity, and high pressure drop. SiO2 was wrapped in the inner layer, unable to play a physical retention and anti-scouring role, and would also block internal pores, reducing mass transfer efficiency.

[0056] In this invention, a high density of amino reaction sites is provided through the PEI intermediate layer, enabling directional covalent grafting of silanes. This exposes the silicon-oxygen ends outward, allowing for the formation of continuous Si-O-Si covalent bonds with subsequent SiO2. Simultaneously, the three-dimensional branched structure of PEI significantly increases the number of SiO2 nucleation sites, achieving higher loading and more uniform distribution. SiO2 is covalently anchored to the PEI surface in the form of discrete nanoparticles, forming a uniformly distributed rigid wear-resistant lattice. This significantly enhances the interfacial bonding strength and effectively improves its resistance to abrasive erosion.

[0057] By introducing hydrophobic alkyl groups into the outermost layer, the wettability of the oil phase is further improved and the permeation resistance is reduced. At the same time, the adhesion of surface hydroxyl groups to the gum is reduced, and the pore blockage is alleviated. This is a special optimization adapted to engine oil scenarios.

[0058] Example 2 A method for preparing a composite modified wood chip oil filter element material, comprising the following steps: S1. Wood chip pretreatment Weigh out sawdust and add it to a 1 mol / L NaOH solution. Stir at 55 °C for 7 h. After the reaction is complete, filter with a sieve and wash with distilled water until neutral. Dry at 45 °C to obtain alkali-treated sawdust. The ratio of sawdust to NaOH solution is 1 g: 4.5 mL. S2.PEI Modification Alkali-treated sawdust was added to a polyethyleneimine solution with a concentration of 28 g / L, followed by the addition of glutaraldehyde to make the volume fraction of glutaraldehyde in the solution 0.5%. The solution was then shaken at a constant temperature of 30 ℃ for 6 h, filtered, rinsed with distilled water until neutral, and finally dried in an oven at 45 ℃ to obtain PEI-modified sawdust (sawdust-PEI). The ratio of alkali-treated sawdust to polyethyleneimine solution was 1 g: 22 mL. S3. Silica Modification (1) Add sawdust-PEI to dry DMF and mechanically stir to disperse. Add 30 mL of γ-glycidoxypropyltrimethoxysilane (EPPTMS) slowly at a rate of 1 mL / min. Continue stirring for 10 min. In an oil bath at 75 °C, mechanically stir and react for 16 h. After the reaction is complete, filter and collect sawdust. Wash with anhydrous ethanol 4 times and then with deionized water 2 times. Place the washed sawdust in a vacuum drying oven at 60 °C and dry for 6 h to obtain EPPTMS-anchored sawdust-PEI. The ratio of sawdust-PEI, EPPTMS and DMF is 3.5 g: 3 mL: 97 mL. (2) Prepare a 4% neutral silica sol solution (pH 7.0), and add the EPPTMS-anchored wood chips-PEI to the solution. React at 80 °C for 24 h. The ratio of the amount of EPPTMS-anchored wood chips-PEI to the amount of neutral silica sol solution is 1 g: 20 mL. S4. Post-processing Weigh 2% of the dry silica mass in the neutral silica sol solution as methyltrimethoxysilane, dissolve it in 3 times its volume of anhydrous ethanol, adjust the pH to 4.5 by adding dilute acetic acid dropwise, and pre-hydrolyze at room temperature for 20 min; then add the pre-hydrolyzed solution dropwise to the silica modification reaction system, and continue the reaction at 75 ℃ for 6 h.

[0059] Example 3 A method for preparing a composite modified wood chip oil filter element material, comprising the following steps: S1. Wood chip pretreatment Weigh out sawdust and add it to a 1 mol / L NaOH solution. Stir at 65 °C for 5 h. After the reaction is complete, filter with a sieve and wash with distilled water until neutral. Dry at 55 °C to obtain alkali-treated sawdust. The ratio of sawdust to NaOH solution is 1 g: 5.5 mL. S2.PEI Modification Alkali-treated sawdust was added to a polyethyleneimine solution with a concentration of 32 g / L, followed by the addition of glutaraldehyde to make the volume fraction of glutaraldehyde in the solution 0.5%. The solution was then shaken at a constant temperature of 30 ℃ for 6 h, filtered, rinsed with distilled water until neutral, and finally dried in an oven at 55 ℃ to obtain PEI-modified sawdust (sawdust-PEI). The ratio of alkali-treated sawdust to polyethyleneimine solution was 1 g: 26 mL. S3. Silica Modification (1) Add sawdust-PEI to dry DMF and mechanically stir to disperse. Add 30 mL of γ-glycidoxypropyltrimethoxysilane (EPPTMS) slowly at a rate of 2 mL / min. Continue stirring for 10 min. In an oil bath at 85 °C, mechanically stir and react for 12 h. After the reaction is complete, filter and collect sawdust. Wash with anhydrous ethanol 4 times and then with deionized water 2 times. Place the washed sawdust in a vacuum drying oven at 60 °C and dry for 6 h to obtain EPPTMS-anchored sawdust-PEI. The ratio of sawdust-PEI, EPPTMS and DMF is 4.5 g: 3 mL: 97 mL. (2) Prepare a 6% neutral silica sol solution (pH 7.0), and add the EPPTMS-anchored wood chips-PEI to the solution. React at 80 °C for 24 h. The ratio of the amount of EPPTMS-anchored wood chips-PEI to the amount of neutral silica sol solution is 1 g: 30 mL. S4. Post-processing Weigh 5% of the dry silica mass in the neutral silica sol solution as methyltrimethoxysilane, dissolve it in 5 times its volume of anhydrous ethanol, adjust the pH to 5.0 by adding dilute acetic acid dropwise, and pre-hydrolyze at room temperature for 40 min; then add the pre-hydrolyzed solution dropwise to the silica modification reaction system, and continue the reaction at 85 ℃ for 3 h.

Claims

1. A method for preparing a composite modified wood chip oil filter material, characterized in that: Wood chips were pretreated with alkali, then grafted with polyethyleneimine (PEI) to obtain wood chip-PEI, then modified with SiO2 loading using a neutral silica sol solution, and finally post-treated with methyltrimethoxysilane (MTMS) to obtain a wood chip oil filter material modified with PEI and SiO2.

2. The preparation method of the composite modified wood chip oil filter material as described in claim 1, characterized in that: The alkali pretreatment involves weighing sawdust, adding it to a NaOH solution, stirring at 55-65 °C for 5-7 hours, and then washing and drying the sawdust after the reaction is complete to obtain alkali-treated sawdust.

3. A method for preparing a composite modified wood chip oil filter material as described in claim 1 or 2, characterized in that: The ratio of sawdust to NaOH solution is 1g:4.5~5.5mL, and the concentration of NaOH solution is 1mol / L.

4. The preparation method of the composite modified wood chip oil filter element material as described in claim 3, characterized in that: The grafting modification involves adding alkali-treated sawdust to a polyethyleneimine solution, then adding glutaraldehyde, shaking at 30 ℃ for 6 h, filtering, rinsing with distilled water until neutral, and drying to obtain sawdust-PEI.

5. The preparation method of the composite modified wood chip oil filter element material as described in claim 4, characterized in that: The SiO2 loading modification involves first anchoring the wood chips-PEI with γ-glycidyl etheroxypropyltrimethoxysilane EPPTMS, and then placing them in a neutral silica sol solution for loading reaction.

6. The method for preparing a composite modified wood chip oil filter element material as described in claim 5, characterized in that: The anchoring treatment involves adding sawdust-PEI to dry DMF and mechanically stirring to disperse it. Then, 30 mL of γ-glycidyl etheroxypropyltrimethoxysilane EPPTMS is slowly added dropwise at a rate of 1-2 mL / min. The mixture is stirred for 10 min and then reacted in an oil bath at 75-85 °C with mechanical stirring for 12-16 h. After washing and drying, EPPTMS-anchored sawdust-PEI is obtained.

7. A method for preparing a composite modified wood chip oil filter element material as described in claim 6, characterized in that: During the loading reaction, a 4-6% neutral silica sol solution was prepared, and EPPTMS-anchored wood chips-PEI were added to the solution. The reaction was carried out at 75-85 °C for 24 h.

8. The method for preparing a composite modified wood chip oil filter material as described in claim 7, characterized in that: The post-treatment involves weighing methyltrimethoxysilane at 2%–5% of the dry silica mass in the neutral silica sol solution, dissolving it in 3–5 times its volume of anhydrous ethanol, adjusting the pH to 4.5–5.0 with dilute acetic acid, and pre-hydrolyzing at room temperature for 20–40 minutes. The pre-hydrolyzed solution is then added dropwise to the silica-modified reaction system, and the reaction is continued at 75–85 °C for 3–6 hours.